The Integration of Wakelet Platform in Analytical Exposition Writing Performance - Prihardini, Fariha Auliya Putri (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2025)
This study aims to determine the effectiveness of the digital platform Wakelet in improving students' analytical exposition writing performance by evaluating the overall improvement in students’ written work and identifying the writing component with the highest gain. The research employed a quantitative approach with a pre-experimental design involving one group of eleventh-grade students at a public senior high school in Surabaya. Students received treatment through the use of Wakelet as a writing learning medium, which facilitated the visual process of collecting, organizing, and structuring ideas. Data were obtained through pre-tests and post-tests and analyzed using descriptive statistics, paired sample t-tests, and effect size calculation. The results revealed a significant difference between the pre-test and post-test scores (p = 0.037) with a moderate effect size of 0.400. Among the five assessed components, students showed the greatest improvement in organization (1.96), followed by vocabulary (1.18), content (0.47), mechanics (0.09), and language use (0.04). These findings indicate that Wakelet can serve as an engaging and effective digital platform to help students develop critical thinking and more structured analytical exposition writing skills. Therefore, integrating Wakelet into English language teaching is considered beneficial in the EFL context.